Visible-light induced photo-click and release strategy between monoarylsydnone and phenoxylfumarate. Issue 66 (5th August 2021) - Liu, Hui; Zheng, Tingting; Zheng, Yuanqin; Li, Baolin; Xie, Xinyu; Shen, Xin; Zhao, Xiaohu; Yu, Zhipeng
Abstract : A visible-light induced photo-click and release approach between monoarylsydnone and phenoxylfumarate was established to realize a precise dual fluorescence turn-on under light control. Abstract : We report a visible-light induced photo-click and release platform between monoarylsydnone (MASyd) and phenoxylfumarates. The pyrazoline produced by the cycloaddition undergoes a photo-aromatization to form a fluorescent pyrazole. Meanwhile, the photo-aromatization also serves as the driving force to release fluorophores that are quenched in the form of phenoxylfumarates.